Unani medical tourism in India: scope, influential factors, development strategies - Rabbani, Mumtaz; Hashim, Khairusy Syakirin Has-Yun; Muflih, Betania Kartika (HH Publisher, 2020)
India is highly prosperous in a wide network of both conventional and alternative medicinal range. The term medical tourism has become famous due to its urgent necessity and desperate requirement among medical seekers. Herbal healthcare therapies are rapidly gaining ethical significance to suffice the medical tourists’ needs. This paper focuses on the amalgamation of Unani medical system with tourism. Furthermore, it identifies the components of health in Unani system along with the factors determining medical tourists to choose this therapy with both domestic and international respondents. Finally, this study concludes with elements affecting travel frequency among medical tourists and the scope of Unani medical tourism in India. Thus, striving to find the best solution to promote Unani tourism and a healthy lifestyle